2005
DOI: 10.1542/peds.2004-2851
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Neurocognitive Changes Before, During, and After Hyperbaric Oxygen Therapy in a Case of Fetal Alcohol Syndrome

Abstract: ABSTRACT. Fetal alcohol syndrome (FAS) is the most common nonhereditary cause of mental retardation, with deficits in general intellectual functioning, learning, memory, attention, and problem-solving. Presented here is the first case in which measured neurocognitive abilities were determined before, during, and after hyperbaric oxygen therapy in a case of FAS involving a teenage male patient. Memory, reaction time, and visual motor speed assessments were compared. After 40 hyperbaric treatments with 100% oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…HBOT involves the inhalation of 100% oxygen in a pressurized chamber, usually above one atmosphere absolute (ATA). It has been shown that HBOT can lead to improved functioning in various neurological populations that show cerebral hypoperfusion including stroke (Nighoghossian et al 1995), cerebral palsy (Montgomery et al 1999), chronically brain injured (Golden et al 2002), and even a teenage male with Fetal Alcohol Syndrome (Stoller 2005). Rossignol and Rossignol (2006) have suggested that the increased oxygen delivered by HBOT could counteract the hypoxia caused by hypoperfusion, and lead to a reduction in symptoms of autism.…”
Section: Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%
“…HBOT involves the inhalation of 100% oxygen in a pressurized chamber, usually above one atmosphere absolute (ATA). It has been shown that HBOT can lead to improved functioning in various neurological populations that show cerebral hypoperfusion including stroke (Nighoghossian et al 1995), cerebral palsy (Montgomery et al 1999), chronically brain injured (Golden et al 2002), and even a teenage male with Fetal Alcohol Syndrome (Stoller 2005). Rossignol and Rossignol (2006) have suggested that the increased oxygen delivered by HBOT could counteract the hypoxia caused by hypoperfusion, and lead to a reduction in symptoms of autism.…”
Section: Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%
“…Many clinical applications of HBOT are at higher pressures (over 2.0 ATA) including treatment of decompression sickness, arterial gas embolism, carbon monoxide poisoning [10], amyotrophic lateral sclerosis [11], and complex regional pain syndrome [12]. However, HBOT has also been used at lower pressures (1.5 ATA or less) with clinical success in conditions including fetal alcohol syndrome [13] and ischemic brain injury [14]. HBOT at 1.5 ATA was utilized in a prospective trial of 168 patients with closed head trauma with a significant reduction in mortality (32% versus 17%) [15].…”
Section: Overview Of Hyperbaric Oxygen Therapymentioning
confidence: 99%
“…HBOT is generally considered safe [17] at oxygen pressures below 3.0 ATA and with treatment durations of less than 120 min [10,13,24]. The use of HBOT in children appears generally safe, even at pressures of 2.0 ATA for 2 hours per day for up to 40 sessions [25].…”
Section: Overview Of Hyperbaric Oxygen Therapymentioning
confidence: 99%
See 2 more Smart Citations